Volume-outcome relationship in corrective surgery for Hirschsprung’s disease: a systematic literature review of direct evidence and an overview of indirect evidence - Solari, Valeria; Boemers, Thomas; Schmiedeke, Eberhard; Knoefel, Wolfram Trudo; Boettcher, Michael; Jenetzky, Ekkehart; Wilms, Miriam (Pediatric surgery international, 2025)
Hirschsprung’s disease (HD) is a rare congenital condition requiring complex corrective surgery. We reviewed available direct evidence on the volume-outcome relationship for HD corrective surgery and assessed the applicability of indirect evidence based on GRADE (Grading of Recommendations Assessment, Development, and Evaluation) recommendations for rare diseases. Three retrospective cohort studies analysing the volume-outcome relationship for HD surgery met the inclusion criteria. In all studies, the high-volume threshold was below 12 HD corrective surgeries per year. No significant volume-outcome relationship was found for outcomes such as readmission or intestinal perforation. Faecal incontinence was not assessed. No risk-adjustment was performed. We applied the GRADE framework and explored indirect evidence from adult colorectal surgery, which shares technical similarities and complexity with HD corrective procedures. Multiple studies in adult colorectal surgery demonstrate a clear volume-outcome relationship, with improved outcomes mostly observed in centres performing more than 20 rectal resections annually. Direct evidence for a volume-outcome relationship in HD surgery cannot be established or refuted due to low caseloads and decentralization. Indirect evidence from adult colorectal surgery with comparable case complexity and the same core outcome parameters suggests the presence of a volume-outcome relationship in HD corrective surgery.
Der Autor Michael Boettcher ist in der Verfasserangabe fälschlich als Michael Böttcher geschrieben
Online veröffentlicht: 21. Juli 2025
Gesehen am 22.09.2025